Digestibility and changes to structural characteristics of green banana starch during in vitro digestion. (July 2015) - Jiang, Huanhuan; Zhang, Yayuan; Hong, Yan; Bi, Yu; Gu, Zhengbiao; Cheng, Li; Li, Zhaofeng; Li, Caiming
Abstract: Green banana starch is well known as a good source of a digestion-resistant starch. Less is known, however, regarding structural transformations during digestion and causal relationships between the digestibility and structural features of banana starch. In this study, two varieties of green banana starches were found to have high resistant fractions of up to 77% and high amylose contents (about 30%). The structures at different digestion stages were characterized using scanning electron microscopy, X-ray diffraction, Fourier transform infrared spectroscopy, and differential scanning calorimetry. Both starches showed C-type crystallinity. The A-type polymorph of banana C-type starch was hydrolyzed more rapidly than the B-type polymorph. The amylose content and crystallinity decreased slightly after digestion, corresponding to changes visible in micrographs during digestion, suggesting that both amorphous and crystalline structures were digested simultaneously and that the structure in the external region of banana starch granules was difficult to digest. Moreover, the chain-length distribution of amylopectin suggested that the high branching, long internal chains, and large proportion of short chains made banana starch resistant to digestion. Graphical abstract: Highlights: Raw banana starches with high content of RS showed large granule size. Banana starches presented high amylose content and more short chains. CB -type banana starch presented more resistant to digestion. The chains (DP 6–24) of banana starch reduced after digestion.